Experimental Study: Back Movement Technique on Beta-Endorphin Levels and Fetal Well-Being - Saptyani, Putri Maretyara; Farkhah, Laeli; Syamsiah, Resti Ikhda (GLOBAL HEALTH SCIENCE GROUP, 2024)
Background: One of the discomforts in the third trimester of pregnancy is lower back pain. This can affect a woman's quality of life during late pre One of the discomforts in the third trimester of pregnancy is lower back pain. This can affect a woman's quality of life during late pregnancy and the early postpartum period. The prevalence of back pain during pregnancy can reach 80%. Treatment using drugs during pregnancy can also cause side effects. The movements in the back movement technique are said to be able to overcome back pain in pregnant women. Research Objective to prove the use of the back movement technique to increase beta endorphin levels and welfare fetus in third trimester pregnant women. This type of research is a Quasy Experiment with a Pretest-Posttest with Control Group. The sample was pregnant women in the third trimester with lower back pain in the Gubug II Community Health Center area, Grobogan, totaling 40 respondents using consecutive sampling technique. Univariate and bivariate data analysis using the Independent T Test and Man Whitney. There was an increase in beta endorphin levels before it was 146.00 ng/ml and after the back movement technique it was 375.21 ng/ml (p = 0.001). Giving the back movement technique was stated to be within normal limits for fetal heart rate and fetal movement (p > 0.05). Back movement technique has been proven to increase beta endorphin levels in pregnant women in the third trimester and is stated safe seen from normal limits for fetal heart rate and fetal movement. gnancy and the early postpartum period. The prevalence of back pain during pregnancy can reach 80%. Treatment using drugs during pregnancy can also cause side effects. The movements in the back movement technique are said to be able to overcome back pain in pregnant women. Research Objective: To prove the use of the back movement technique to increase beta endorphin levels and welfare fetus in third trimester pregnant women Research Method: This type of research is a Quasy Experiment with a Pretest-Posttest with Control Group Design . The sample was pregnant women in the third trimester with lower back pain in the Gubug II Community Health Center area, Grobogan, totaling 40 respondents using consecutive sampling technique . Univariate and bivariate data analysis using the Independent T Test and Man Whitney . Research Results: There was an increase in beta endorphin levels before it was 146.00 ng/ml and after the back movement technique it was 375.21 ng/ml ( p = 0.001). Giving the back movement technique was stated to be within normal limits for fetal heart rate and fetal movement ( p > 0.05) Conclusion: Back movement technique has been proven to increase beta endorphin levels in pregnant women in the third trimester and is stated safe seen from normal limits for fetal heart rate and fetal movement Keywords: low back pain , beta endorphin , fetal well-being